Cross-sectional study of prevalence and risk factors, and a cost-effectiveness evaluation of screening and preventive treatment strategies for latent tuberculosis among migrants in Singapore - Lim, Vanessa W (BMJ Open, 2021)
OBJECTIVES: WHO recommends that low burden countries consider systematic screening and treatment of latent tuberculosis infection (LTBI) in migrants from high incidence countries. We aimed to determine LTBI prevalence and risk factors and evaluate cost-effectiveness of screening and treating LTBI in migrants to Singapore from a government payer perspective. DESIGN: Cross-sectional study and cost-effectiveness analysis. SETTING: Migrants in Singapore. PARTICIPANTS: 3618 migrants who were between 20 and 50 years old, have not worked in Singapore previously and stayed in Singapore for less than a year were recruited. PRIMARY AND SECONDARY OUTCOME MEASURES: Costs, quality-adjusted life-years (QALYs), threshold length of stay, incremental cost-effectiveness ratios (ICERs), cost per active TB case averted. RESULTS: Of 3584 migrants surveyed, 20.4% had positive interferon-gamma release assay (IGRA) results, with the highest positivity in Filipinos (33.2%). Higher LTBI prevalence was significantly associated with age, marital status and past TB exposure. The cost-effectiveness model projected an ICER of S$57 116 per QALY and S$12 422 per active TB case averted for screening and treating LTBI with 3 months once weekly isoniazid and rifapentine combination regimen treatment compared with no screening over a 50-year time horizon. ICER was most sensitive to the cohort’s length of stay in Singapore, yearly disease progression rates from LTBI to active TB, followed by the cost of IGRA testing. CONCLUSIONS: For LTBI screening and treatment of migrants to be cost-effective, migrants from high burden countries would have to stay in Singapore for ~50 years. Risk-stratified approaches based on projected length of stay and country of origin and/or age group can be considered.